Characterisation and crystallisation kinetics of glass ceramics developed from Erdemir blast furnace slags containing Cr2O3 and TiO2 nucleants - (:unkn) unknown (MANEY PUBLISHING, 2009)
Glass ceramic materials were developed from blast furnace slags doped with 5 wt-% TiO2, 10 wt-% TiO2, 5 wt-% Cr2O3 and 5 wt-% TiO2 + 5 wt-% Cr2O3. Based on differential thermal analyses and optical microscopy, optimum conditions were determined as 18 h at 780 degrees C and 20 min at 910 degrees C, for nucleation and crystallisation respectively. X-ray diffraction investigations were carried out on the as nucleated and as crystallised samples. Akermanite (2CaO center dot MgO center dot 2SiO(2)) and gehlenite (2CaO center dot Al2O3 center dot SiO2) in addition to nucleant phases (TiO2 and/or Cr2O3) appeared in crystallised samples. Scanning electron microscopy and energy dispersive spectroscopy revealed the presence of TiO2 rich and Cr2O3 rich particles in the matrix after nucleation and crystallisation. Crystalline phases and nucleant (TiO2 or Cr2O3) existed only on the surface of the sample. Based on differential thermal analyses results, Avrami n values were calculated to vary between 1.04 and 1.22, indicating surface crystallisation for which activation energies were found to vary between 290 and 334 kJ mol(-1).
Keywords: Blast furnace slag; Glass ceramics; TiO2 and Cr2O3 nucleants; Microstructure; Crystallisation kinetics; DIFFERENTIAL THERMAL-ANALYSIS; WASTES